A Morphological Study On Affixes In English Song Lyrics On The Resistance Album Composed By Muse - Setyawan, Yanuar Bondhan, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2014)
This study aims at describing the types of affixes in English song lyrics on the Resistance album composed by Muse; to classifying types of affixes work in the English song lyrics on Resistance album by Muse; to describing the word-class of all words consisting of affixes in the English song lyrics on Resistance album by Muse. The type of this research is descriptive qualitative research. In collecting the data, the writer uses documentation. There are five steps to collect data, namely: reading, underlying or marking sentences in the English song lyrics of Resistance album by Muse which contain affixes, classifying the types of the words which contain affixes in English song lyrics of Resistance album by Muse, the writer writes again the data systematically, the researcher makes code for every data. The collected data are analyzed by using morphological theory that purposed by Katamba. The result of the research is 188 data of words containing affixes in the English song lyrics on Resistance Album by Muse. There are 30 data of words containing derivational affixes or 15.96% and 158 data of words containing inflectional affixes or 84.04% from 188 data. finds 30 data or 7.86% derivational affixes tha t consists of prefix pro 1 data or 0.53%, prefix dis 1 data or 0.53%, prefix a 1 data or 0.53% and prefix re also 1 data or 0.53%. And then suffix cy 2 data or 1.06%, suffix ful 2 data or 1.06, suffix ion 1 data or 0.53%, suffix ed 2 data or 1.06%. suffix dom 1 data or 0.53%, suffix ly 7 data or 3.72 %, suffix ness 2 data or 1.06% , suffix ion 2 data or 1.06%, suffix acy 1 data or 0.53%, suffix th 3 data or 1.60%, suffix ical 1 data or 0.53% and suffix less 2 data or 1.06%.In conclusion, the meaning of affixes that used in the data source is indicator of changing the class of the category. At the end of analysis, the researcher finds that the addition of affixes into the word would influence either the meaning of the existing word.